Description of a new sand lance species, Bleekeria murtii (Perciformes: Ammodytidae) from India - Joshi, K K; Zachariah, P. U; Kanthan, P (Indian Journal of Fisheries, 2012)
A new fish species of the genus Bleekeria was collected by trawl nets off Tuticorin from a depth of 20-30 m. Bleekeria murtii is characterized by 34-39 dorsal rays, 12-16 anal rays, 80-108 lateral line scales, high head length (21.1-23.2 in SL), smaller eye diameter (2.45-5.37 mm) and high body height (8.7-19.7 mm). The species-specific characters, colour pattern and morphometric variations are described in detail.